On regular graph,thathas two types of facesthat havingtwo consecutive numbers of edges (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is known that any three - Regulargraph, planar and connected, and all the faces in it arepentagonal or hexagonal, thenthe number of pentagons in it is double the number of hexagonaledges, i.e. 12. [6].The purpose of this paper is to prove the following:Given ans-regular graph,planar and connected, and all the faces in it contain only (l)or(l+1)edges, also